Hypertension differentially impacts cognition in men and women in early midlife. Issue 1 (29th September 2022) - Shields, Hannah L.; Konishi, Kyoko; Aroner, Sarah; Aizley, Harlyn; Remington, Anne; Lee, Hang; Buka, Stephen; Goldstein, Jill M.
Abstract: The current study aimed to understand how sex differences in the timing of hypertension onset contribute to early midlife risk for cognitive decline that may differ by sex and whether sex‐dependent advantages in normotensive populations are influenced by the presence of hypertension. One hundred and ninety‐five adults aged 45–55 from the New England Family Study underwent neuropsychological testing to assess attention, executive function, and memory. Physician‐diagnosed hypertension status was self‐reported via questionnaire. Mid‐adulthood hypertension was associated with worse performance on measures of attention and memory, but the cognitive domains impacted varied by sex. Hypertension was associated with only attention in men, whereas in women it was associated with attention and associative and working memory. Sex differences in midlife cognitive performance found in normotensive adults were attenuated in those with hypertension. Our results underscore the importance of accounting for sex when assessing the impact of hypertension on midlife cognition that could be indicative of later decline and risk for cognitive impairment and dementia, given hypertension is an independent risk factor.